Genetic Variation in SP-A2 Leads to Differential Binding to Mycoplasma pneumoniae Membranes and Regulation of Host Responses - Ledford, Julie G; Voelker, Dennis R; Addison, Kenneth J; Wang, Ying; Nikam, Vinayak S; Degan, Simone; Kandasamy, Pitachaimani; Tanyaratsrisakul, Sasipa; Fischer, Bernard M; Kraft, Monica; Hollingsworth, John W (The Journal of immunology (1950), 2015)
Mycoplasma pneumoniae is an extracellular pathogen that colonizes mucosal surfaces of the respiratory tract and is associated with asthma exacerbations. Previous reports demonstrate that surfactant protein-A (SP-A) binds live M. pneumoniae and mycoplasma membrane fractions (MMF) with high affinity. Humans express a repertoire of single–amino acid genetic variants of SP-A that may be associated with lung disease, and our findings demonstrate that allelic differences in SP-A2 (Gln223Lys) affect the binding to MMF. We show that SP-A−/− mice are more susceptible to MMF exposure and have significant increases in mucin production and neutrophil recruitment. Novel humanized SP-A2–transgenic mice harboring the hSP-A2 223K allele exhibit reduced neutrophil influx and mucin production in the lungs when challenged with MMF compared with SP-A−/− mice. Conversely, mice expressing hSP-A2 223Q have increased neutrophil influx and mucin production that are similar to SP-A−/− mice. Using tracheal epithelial cell cultures, we show that enhanced mucin production to MMF occurs in the absence of SP-A and is not dependent upon neutrophil recruitment. Increased phosphorylation of the epidermal growth factor receptor (EGFR) was evident in the lungs of MMF-challenged mice when SP-A was absent. Pharmacologic inhibition of EGFR prior to MMF challenge dramatically reduced mucin production in SP-A−/− mice. These findings suggest a protective role for SP-A in limiting MMF-stimulated mucin production that occurs through interference with EGFR-mediated signaling. SP-A interaction with the EGFR signaling pathway appears to occur in an allele-specific manner that may have important implications for SP-A polymorphisms in human diseases.